A phase I study on the combination of neoadjuvant radiotherapy plus pazopanib in patients with locally advanced soft tissue sarcoma of the extremities. (September 2015) - Haas, Rick L. M.; Gelderblom, Hans; Sleijfer, Stefan; van Boven, Hester H.; Scholten, Astrid; Dewit, Luc; Borst, Gerben; van der Hage, Jos; Kerst, J. Martijn; Nout, Remi A.; Hartgrink, Henk H.; de Pree, Ilse; et al.
Abstract Accumulating evidence suggests significant synergism combining radiotherapy (RT) with angiogenesis targeted therapies. This multicenter prospective phase I clinical trial established the safety profile and recommended dose for further studies of pazopanib concurrent with preoperative RT in patients with extremity soft tissue sarcomas (ESTS) in curative setting. Methods. Patients with deep seated intermediate and high grade sarcomas, ≥ 5 cm, received once daily pazopanib (dose-escalation cohorts 400 mg, 600 mg and 800 mg) for 6 weeks and 50 Gy preoperative RT starting Day 8. Surgery was performed 5–7 weeks later. Toxicity was scored according to CTC criteria 4.0. Dose limiting toxicities (DLT) were divided into two separate sets; DLT-I being toxicities occurring during the 6-week chemoradiotherapy period within the radiation portals until day of surgery (designated as DLT-I) and those occurring perioperatively until Day 21 after surgery (DLT-II). Results. A total of 12 patients were enrolled, 11 were evaluable (3 females and 8 males, median age 58 years, range 24–78 years, median tumor size 9 cm, range 5–15 cm). Ten underwent surgery. No increased toxicity inside the radiation fields was seen, but two of 10 patients (one each in the 400 mg and 600 mg cohorts) showed delayed wound healing after surgery. None of the patients showed significant volume reductions after RT. Evaluation of the resection specimen showed pathological (near) complete responses (≥ 95% necrosis rate) in four of 10 cases. Unexpectedly, grade 3 + hepatotoxicity led to premature pazopanib interruption in three of 11 (27%) of cases. Conclusion. Apart from hepatotoxicity, neoadjuvant pazopanib 800 mg daily in combination with 50 Gy seems tolerable; the regimen appears to demonstrate promising activity in ESTS and is the recommended dose for further studies.